-(9-3x)=11

Simple and best practice solution for -(9-3x)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(9-3x)=11 equation:


Simplifying
-1(9 + -3x) = 11
(9 * -1 + -3x * -1) = 11
(-9 + 3x) = 11

Solving
-9 + 3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 3x = 11 + 9

Combine like terms: -9 + 9 = 0
0 + 3x = 11 + 9
3x = 11 + 9

Combine like terms: 11 + 9 = 20
3x = 20

Divide each side by '3'.
x = 6.666666667

Simplifying
x = 6.666666667

See similar equations:

| 0.20(y-6)+0.06y=0.18y-0.03(30) | | -4-6k+6-8=-6-6k | | (2x)+3=(4x)-3 | | 8(4k+1)=15k+6(10k-13) | | 6t^2-26t+22=0 | | 0.75x+5y=20 | | 8x-3x^2+2x= | | 12x+20=-40 | | (-1x)+2=2+(-4x) | | -4s=-5(s-5) | | 4x^2+160=0 | | 24+x=54 | | (fg)(x)=(5x-2)(3x^2) | | 38+5x=-32 | | 6(x-4)+3x=5(2x+8)-14 | | 9x+7=7x+37 | | 12+4q+1=5(q+5) | | c+1-3=-21 | | .05t+.012(t+1)=.57 | | -4(17y-15)=-6(4+12y) | | 2(1.43)-y=7 | | G(5n)=2x^2-5 | | (-4x)+6=(-2x)+10 | | 20g-16=8(6g+19) | | -(5x-8)-(6x-3)+4=-6(x-4)-(9x+9)+3 | | 5x+(-2)=2x+10 | | -14.18-16.6v=-16.3v-9.68 | | 2x=84-12 | | s+4=7.3 | | -2(n+1)=19+n | | 3(2x+7)=-48+63 | | 2z=-4z-2 |

Equations solver categories